2015
DOI: 10.1016/j.scitotenv.2015.03.075
|View full text |Cite
|
Sign up to set email alerts
|

In situ assessment of phyto and zooavailability of trace elements: A complementary approach to chemical extraction procedures

Abstract: For an accurate risk assessment of sites contaminated by trace elements (TE), measurements of bioavailability must be performed. This is routinely achieved using the standardized 0.01M CaCl2 method. However, the suitability of chemical extractions as proxies of bioavailability is questionable. We analyzed the correlations between chemically estimated TE bioavailability and TE actually accumulated by coupling plant and snails bioindicators. Results showed a better correlation between plant TE contents and CaCl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This effect was probably indirect, through the consumption of Cd-contaminated plants. These animals feed mainly on plants (Dallinger et al 2004 ; Pauget et al 2015 ), and a low soil pH increases Cd solubility and availability, particularly for uptake by plants (Erikson et al 1996 ). It is also possible that the ingestion of soil, and Cd uptake via the foot epithelium could contribute, at least to some degree, to this effect (Coeurdassier et al 2002 ; Pauget et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…This effect was probably indirect, through the consumption of Cd-contaminated plants. These animals feed mainly on plants (Dallinger et al 2004 ; Pauget et al 2015 ), and a low soil pH increases Cd solubility and availability, particularly for uptake by plants (Erikson et al 1996 ). It is also possible that the ingestion of soil, and Cd uptake via the foot epithelium could contribute, at least to some degree, to this effect (Coeurdassier et al 2002 ; Pauget et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…rhizospheric processes) and acquisition sources, i.e. superficial/deep soil layers for plants, and superficial soil and plant material for snails (Pauget et al, 2015). Thus, the authors concluded that bioindicators should complement chemical procedures to get better insights into contaminated areas.…”
Section: Methods For Predicting Bioavailabilitymentioning
confidence: 99%
“…Although these correlations may occur for some elements, such as Cd, plant uptake of other metals (e.g. Cu, Ni and Zn) was shown to be poorly correlated to the -easily extracted‖ fraction in soils determined via the CaCl 2 method (Pauget et al, 2015).…”
Section: Ion Exchangementioning
confidence: 95%
“…and the mutable physiological conditions of exposed organisms (diet, age, metabolic rate, and reproductive state), the bioavailability, uptake, and bioaccumulation of metals are dynamic processes [10]. Recent studies analyzing the possible correlations between metal bioavailability estimated chemically in urban soil and the amount actually accumulated in soil fauna (e.g., [11,12]) have found that the metal content in different soil fractions does not allow to predict its bioaccumulation. As discussed by Pauget et al [11], the chemical analysis of soil only informs about the easiness of metal leaching by weak extractions (i.e., the environmental availability) and not about the actual bioavailability and/or bioaccumulation, which also depend on the physiological traits and conditions of the target organisms [13].…”
Section: Introductionmentioning
confidence: 99%